Analyzing the Students’ Errors in Writing Procedure Text - Nur Malikul Mulki R; Sahril Nur; La Sunra (Journal of Excellence in English Language Education, 2022)
The aims of this research include: (1) to identify the types of errors made by 12th grade of the students SMKN 2 Gowa in writing procedure text, (2) to find out the source of error, (3) to provide suggestions to avoid or reduce errors. This research used descriptive qualitative method. The instrument used in collecting the data were writing test and interview. The population of this research was the 12th grade of the students SMAN 2 Gowa culinary art major. The subject was population which consisted of 43 students. In analyzing the data, the researcher found that the students’ errors in writing a procedure text. The types of errors discovered, namely verb tenses, sentence structure, connector, passive construction, subject-verb agreement, word order, articles, diction, mechanics, and unclear idea. The sources of errors include Inter-lingual, Intra-lingual transfer, context learning, and communicative strategy. The suggestions to discover the errors in writing procedure texts were about method of teaching, material, and motivation.